(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
This global climate in the article change and energy resources limitedness under the circumstances energy saver of technologies architecture and construction in the field importance illuminated . Modern buildings in design energy efficiency provide for the purpose applicable construction shell insulation , energy economical windows, high effective engineering systems and again recovering energy sources integration technologies analysis Also, energy saving economic , ecological and operational advantages of the building to live convenience and stable internal environment in creation place seeing published. In the article passive and asset design approaches The importance of energy is also highlighted . effective buildings build of reaching stable development for important factor that based on given.